Debut crimes and chronic offenders in Queensland - Townsley, Michael (Journal of criminology, 2023)
We investigate whether the type of crime committed early in an individual's career has a bearing on patterns of subsequent offending (the so-called debut hypothesis) in an Australian setting. Police-recorded crime data from 2008 to 2020 were used and partitioned into cohorts based on the year of the first offence. We computed, for each cohort, the rate at which individuals progressed to established criminal careers conditioned by their first recorded offence. Individuals who commit burglary, vehicle theft, or robbery as their first recorded offence were observed to become chronic offenders at higher rates than those who commit other types of first offences. We also demonstrated that this relationship exists for other dimensions of the criminal career and is time stable. The policy implications of our findings suggest that a combination of opportunity reduction and diversionary policies has the potential to substantially reduce the prospects of chronic criminal careers and their societal impact.